2020
DOI: 10.1017/s095026882000179x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of severe cases with COVID-19: a meta-analysis

Abstract: Our study aimed to systematically analyse the risk factors of coronavirus disease 2019 (COVID-19) patients with severe disease. An electronic search in eight databases to identify studies describing severe or critically ill COVID-19 patients from 1 January 2020 to 3 April 2020. In the end, we meta-analysed 40 studies involving 5872 COVID-19 patients. The average age was higher in severe COVID-19 patients (weighted mean difference; WMD = 10.69, 95%CI 7.83–13.54). Patients with severe disease showed significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
90
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(128 citation statements)
references
References 25 publications
13
90
0
Order By: Relevance
“…Comorbidities were similar in both groups, while bacterial superinfection, thromboembolic complications and treatment with antibiotics or convalescent plasma were more frequent in ventilated patients (Table 1). As described before 27 , ventilated patients displayed higher plasma concentrations for biomarkers indicating in ammation (CRP, IL-6), liver and muscle dysfunction (LDH, Bilirubin, CK) and intravascular coagulation (D-dimer). Ventilated "dead" patients showed higher leukocyte counts and higher biomarkers for in ammation and liver dysfunction than ventilated "survived" patients (Supplementary Table 1).…”
Section: Clinical Characterization Of Covid-19 Patientssupporting
confidence: 65%
“…Comorbidities were similar in both groups, while bacterial superinfection, thromboembolic complications and treatment with antibiotics or convalescent plasma were more frequent in ventilated patients (Table 1). As described before 27 , ventilated patients displayed higher plasma concentrations for biomarkers indicating in ammation (CRP, IL-6), liver and muscle dysfunction (LDH, Bilirubin, CK) and intravascular coagulation (D-dimer). Ventilated "dead" patients showed higher leukocyte counts and higher biomarkers for in ammation and liver dysfunction than ventilated "survived" patients (Supplementary Table 1).…”
Section: Clinical Characterization Of Covid-19 Patientssupporting
confidence: 65%
“…Age has been reported as a prominent factor regarding the severity of COVID-19 32 36 . One meta-analysis examining 29 studies involving 3411 COVID-19 patients revealed that the age of mild and severe groups is significantly different (weighted mean difference of 10.69) 37 . Age needs to be adjusted to more accurately examine the different characteristics of blood proteome between mild and severe groups.…”
Section: Resultsmentioning
confidence: 99%
“…4,9 Currently, several studies are striving to define the risk factors for the development of severe pneumonia in COVID-19 patients and to identify the factors that can have an impact on patient outcome. 10,11 To date, there are also no studies that have evaluated the nutritional status of patients affected by COVID-19 with bioelectrical impedance analysis (BIA). Given the prognostic value of bioimpedance parameters on different clinical outcomes already demonstrated for other categories of patients, 11,12 it can be assumed that this could also provide useful information in the management of COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%